Strategi Implementasi Sistem Manajemen Anti Penyuapan dalam Mewujudkan Good Governance : (Studi Kasus: Balai Pelatihan Z) - Mohamad Taufiq; Evony Silvino Violita (Owner : Riset dan Jurnal Akuntansi, 2023)
This research aims to evaluate the organizational readiness of Training Center Z if it will implement SNI ISO 37001: 2016 Anti-Bribery Management System to realize good governance. The implementation of the anti-bribery management system is needed because the Z Training Center as a public service work unit cannot be separated from the potential risk of bribery. The anti-bribery management system as one of the instruments of governance is expected to be a system that can prevent, detect, report, and handle potential acts of bribery and realize good governance within the Z Training Center. This research uses the Gap Analysis method in measuring the readiness of the implementation of the anti-bribery management system and the Strengths Weaknesses Opportunities Threats analysis method combined with the Analytical Hierarchy Process to produce a strategy for implementing an anti-bribery management system in the short term, medium term, and long term in order to realize good governance in the Z Training Center environment. The results showed that Training Center Z was not ready to implement an anti-bribery management system because Training Center Z employees had never received training on anti-bribery management systems and there was no risk assessment of bribery, so an implementation strategy was needed to implement and realize good governance. These strategies include conducting anti-bribery management system training to all employees, socializing anti-gratuities, assessing bribery risks, budgeting activities, and making policies/guidelines for implementing anti-bribery management systems. The results of this study are expected to be knowledge for the leadership of the Z Training Center on how readiness and guidance in developing strategies for implementing an anti-bribery management system in order to realize good governance.